Artificial intelligence-based methods for image processing: Artificial intelligence-based methods for image processing - Begmatov, Shohruh; Arabboev, Mukhriddin; Rikhsivoev, Mokhirjon; Nosirov, Nosirov (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract. Artificial intelligence (AI) has revolutionized the field of image processing by introducing advanced techniques for image analysis, enhancement, segmentation, and recognition. This paper comprehensively reviews AI-based methods employed in image processing tasks. It covers various AI techniques, such as machine learning, deep learning, and their applications in medical imaging, computer vision, robotic system, and more.